The Function of Two Brassica napus β-Ketoacyl-CoA Synthases on the Fatty Acid Composition - Dongfang Zhao; Bingqian Zhou; Bo Hong; Jiajun Mao; Hu Chen; Junjie Wu; Li Liao; Chunyun Guan; Mei Guan (Plants)
Rapeseed (Brassica napus L.) is one of the four major oilseed crops in the world and is rich in fatty acids. Changes in the fatty acid composition affect the quality of rapeseed. Fatty acids play various roles in plants, but the functions of the genes involved in the fatty acid composition during plant development remain unclear. β-Ketoacyl-CoA synthase (KCS) is a key enzyme involved in the elongation of fatty acids. Various types of fatty acid products are used to build lipid molecules, such as oils, suberin, wax, and membrane lipids. In B. napus, BnaKCSA8 and BnaKCSC3 belong to the KCS family, but their specific functions remain unclear. This study cloned BnaKCSA8 and BnaKCSC3 from Brassica napus L. and analyzed their functions. The gene structures of BnaKCSA8 and BnaKCSC3 were similar and they were localized to the endoplasmic reticulum (ER). In yeast, overexpression of BnaKCSA8 increased the ratios of palmitoleic acid and oleic acid, while BnaKCSC3 decreased the ratios of oleic acid. In Arabidopsis, overexpression of BnaKCSA8 and BnaKCSC3 lead to an increase in the proportion of linoleic acid and a decrease in the erucic acid. In summary, BnaKCSA8 and BnaKCSC3 altered the composition ratios of fatty acids. These findings lay the foundation for an understanding of the role of KCS in the fatty acids in rapeseed, potentially improving its health and nutritional qualities.